Caught between Risks and Pleasures: Children’s Digital User Profiles, Their Right-Based Experiences and Self-Rights Awareness in Digital Media Areas in the Light of Multicultural Children’s Human Rights Education - Erdem Hareket (Dinamika Ilmu, 2026)
This study investigates the digital user profiles of children, rights-based experiences, and their awareness of digital rights within the framework of the UN Committee on the Rights of the Child’s General Comment No 25. Highlighting the paradoxical position of children as a unique yet underappreciated user group, the research also explores how digital environments impact their well-being and best interests, and why children’s human rights education, suitable for multiculturalism, is important in the digital age. The research data were collected from 1430 children's open-ended questionnaires and one-on-one interviews. The findings reveal that children primarily access digital platforms through tablets and phones, spending one-third of their daytime hours on gaming, entertainment, and social interaction. Emotionally, these experiences oscillate between intense pleasure and anger. While children demonstrate a protective stance toward personal data and recognize the benefits of digital tools for education, communication, and freedom of expression, they face significant risks regarding exposure to violent, sexual, and commercial content. Crucially, the current study identifies a gap in children’s awareness of their digital rights, with many reporting frequent violations through cyberbullying and harassment. The results indicate a disconnect between children's digital user tendencies and their rights awareness, underscoring an urgent need to integrate digital literacy and children’s rights education in digital areas, grounded in intercultural sensitivity, to better protect their interests in an increasingly digitized society.